Influence of Frictional Behavior Under MQL on Cutting Process in Shoulder Milling Ti-6Al-4V - Kondo Hiroyasu; Tamura Shoichi; Matsumura Takashi (International journal of automation technology, 2025)
Titanium alloys are commonly applied to aerospace parts because of their high specific strength, heat resistance, and corrosion resistance. To develop cost-effective and reliable parts, it is crucial to achieve high-quality and productive machining of titanium alloys. It is important to control the cutting force to achieve a good surface finish and minimize tool wear. The interaction between the tool and chip significantly influences the cutting force. This study focuses on the influence of the frictional behavior of minimum quantity lubrication (MQL) on cutting force and chip formation in shoulder milling of Ti-6Al-4V. The milling process under the MQL condition is compared to those under dry and high-pressure flood coolant conditions in the cutting tests. The cutter feed and normal components in the cutting force under the MQL condition become smaller in comparison with those of the other lubrication conditions. Regarding the chip morphology, the curl radius becomes small in milling under the MQL condition, while the chip forms with a large radius in milling under dry condition. This suggests that the small friction coefficient increases the chip flow velocity closer to the rake face in milling under the MQL condition. The effect of lubrication on the cutting force is analyzed with a force model based on the minimum cutting energy. The model is verified through comparison between the simulated and measured cutting forces. Comparative analysis of friction angles in MQL, flood coolant, and dry milling conditions indicates that the angle in MQL milling is reduced by approximately 2° and 3° compared to that in the flood and dry conditions, respectively.